INVENTARISASI BENTUK ORNAMEN KERAJINAN CUKLI LOMBOK SEBAGAI BENTUK PELESTARIAN BUDAYA - Pyo Apriliana Munawarah; L. Aswandi Mahroni G. (SANGKAREANG, 2016)
Lombok is one of accounted areas of tourism because supported by the industry sector, one of them is industry cukli in Mataram city. Craft cukli in Rungkang Jangkuk Sayang-sayang develop into the only sentra cukli craft in West Nusa Tenggara .The purpose of handicrafts is not only in the nasional market but also has been a commodity export .The development of the cukli craft supported by creativity of craftsman in the spot . Nowdays, cukli craft depends on global market that require innovation on shape and expansion ornament required consumers. Acknowledgment of typical cukli ornament Rungkang Jangkuk must surely be calculated and recorded so that the recognition of cukli craft Rungkang Jangkuk will be awake well.This study seeks to identify and analyze the form of cukli ornaments in Rungkang Jangkuk Sayang-Sayang. The continuity characterized by various forms of geometric ornaments, plants, animal, and calligraphic. Cukli craft that are excellent local village until now has not been recorded properly, either in the form of ornaments and relates to issues concerning the development of a characteristic design cukli Rungkang Jangkuk. Therefore investigators applying analytical descriptive study, exposure of survival cukli craft presented descriptively by using a number of qualitative data as a result of interpretation of the forms of ornamentation that characterizes cukli. The Data will be presented through the collection and mapping the form of ornament applied, as well as the development of forms of ornaments in the form of images and tables.